Enhanced kinetics of polysulfide redox reactions on Mo2C/CNT in lithium–sulfur batteries. (16th May 2018) - Razaq, Rameez; Sun, Dan; Xin, Ying; Li, Qian; Huang, Taizhong; Zheng, Lei; Zhang, Zhaoliang; Huang, Yunhui
Abstract: Among different energy storage devices, the lithium–sulfur (Li–S) battery is the subject of recent attention. However, the capacity decay caused by polysulfide shuttle leading to sluggish kinetics of polysulfide redox reactions is the main hindrance for its practical application in Li–S batteries. Herein, molybdenum carbide nanoparticles anchored on carbon nanotubes (Mo2 C/CNT) are reported to serve as an efficient cathode material to enhance the electrochemical kinetics of polysulfide conversion in Li–S batteries. Mo2 C/CNT shows strong adsorption and activation of polar polysulfides and therefore accelerates the redox kinetics of polysulfides, reduces the energy barrier, effectively mitigates the polarization and polysulfide shuttle, thus improving the electrochemical performance. The S-Mo2 C/CNT composite with 70 wt% sulfur loading exhibits high specific discharge capacity (1206 mA h g −1 at 0.5 C), excellent high-rate performance, long cycle life (900 cycles), and outstanding Coulombic efficiency (∼100%) at a high rate (2 C) corresponding to a capacity decay of only 0.05%. Remarkably, the S-Mo2 C/CNT cathode with high areal sulfur loading of 2.5 mg cm −2 exhibits high-rate capacities and stable cycling performance over 100 cycles, offering the potential for use in high energy Li–S batteries.